2015
DOI: 10.1111/joss.12164
|View full text |Cite
|
Sign up to set email alerts
|

Predicting and Understanding Long‐Term Consumer Liking of Standard Versus Novel Chocolate: A Repeated Exposure Study

Abstract: Repeated exposure was investigated for predicting long-term liking of five chocolates products; three novel products, added cinnamon/cardamom, commercial beet flavor or a homemade beet-flavor and two existing products: 70% chocolate and chocolate added liquorice. Ninety-five Danish consumers were exposed daily to one of the five chocolate types during a two-week period, interrupted twice with exposure to odd samples (day 3 and 10). Liking, arousal and complexity were rated. Arousal and perceived complexity rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Although spread wafer was also an unfamiliar product (Table 7), its liking score was relatively high, which could have been affected by brand awareness [34,35] and familiarity with the spread used for filling in the spread wafer. Soerensen et al [36] indicated there was no dynamic liking when novel flavors were added because of a high perceived familiarity with chocolates. In addition, well-known samples were evaluated first, whereas unfamiliar samples were evaluated later in the 'No control' group (Tables 7 and 8).…”
Section: Consumer's Liking and Perceived Intensity Of Samplesmentioning
confidence: 99%
“…Although spread wafer was also an unfamiliar product (Table 7), its liking score was relatively high, which could have been affected by brand awareness [34,35] and familiarity with the spread used for filling in the spread wafer. Soerensen et al [36] indicated there was no dynamic liking when novel flavors were added because of a high perceived familiarity with chocolates. In addition, well-known samples were evaluated first, whereas unfamiliar samples were evaluated later in the 'No control' group (Tables 7 and 8).…”
Section: Consumer's Liking and Perceived Intensity Of Samplesmentioning
confidence: 99%
“…The subjective qualities involve moral, cultural and sensory factors, among others. Consumer liking is a “complex interlinked relationship of underlying factors” and involves many different scientific fields such as psychology, physiology, sociology, chemistry and economics (Soerensen et al ).…”
Section: Introductionmentioning
confidence: 99%
“…This proposition remains to be confirmed, with many existing studies focusing on complexity within food and drinks in terms of subtle 'multiple sensations.' For example, wine with a flavour profile including many different 'notes' (Spence & Wang, 2018), or dark solid chocolate bars altered with different flavourings including beet, cinnamon, cardamon and liquorice (Soerensen et al, 2015), may be described as having high perceived flavour complexity but do not constitute a multi-component food when considering a definition that prescribes a need to have discernible components that differ in composition.…”
Section: Perceived Sensory Complexitymentioning
confidence: 99%
“…Several studies have explored the effect of sensory complexity on hedonic responses to foods. Whilst some have shown no effect of complexity on hedonic response with only a subtle manipulation of flavour (e.g., salty crackers with different added flavourings) (Porcherot & Issanchou, 1998;Soerensen, Waehrens, & Byrne, 2015), others have found a limited effect on liking with a more extreme manipulation (e.g., mashed potatoes with pieces of celery and nutmeg added) (Reverdy, Schlich, Köster, Ginon, & Lange, 2010;Weijzen, Zandstra, Alfieri, & de Graaf, 2008). Notably, Weijzen et al (2008) included test foods that would be considered 'multi-component' (e.g., candy bar with chocolate and nuts).…”
Section: Liking and Enjoymentmentioning
confidence: 99%